2009
DOI: 10.1155/2009/871365
|View full text |Cite
|
Sign up to set email alerts
|

Mood Disorder Due to a General Medical Condition with Manic Features

Abstract: This case report describes a patient with manic and psychotic symptoms who had a history of neurocysticercosis and presented with an episode of hypertensive hydrocephalus in 2003. Despite her history, she was initially treated for primary psychiatric disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Cognitive and psychiatric dysfunctions associated with the presence of hydrocephalus in NC patients, though poorly researched, have been described in several studies [40][41][42][43] and have been explained in terms of the periventricular white matter tracts destruction and changes in neurotransmitters [44][45][46]. One study carried out at our institute showed that 21.5% of NC patients were originally diagnosed with dementia, which became reversible after 6 months of treatment [47].…”
Section: Ich Due To Hydrocephalusmentioning
confidence: 99%
“…Cognitive and psychiatric dysfunctions associated with the presence of hydrocephalus in NC patients, though poorly researched, have been described in several studies [40][41][42][43] and have been explained in terms of the periventricular white matter tracts destruction and changes in neurotransmitters [44][45][46]. One study carried out at our institute showed that 21.5% of NC patients were originally diagnosed with dementia, which became reversible after 6 months of treatment [47].…”
Section: Ich Due To Hydrocephalusmentioning
confidence: 99%
“…To the best of our knowledge, only few cases of patients with neurocysticercosis and mania have been reported,[12] all of them without any further description of the illness course and long-term treatment. In addition, the long-term course of cognitive function of these patients has not yet been investigated.…”
mentioning
confidence: 99%
“…Manic episodes in patients with neurocysticercosis have been treated with risperidone and/or carbamazepine[1] or valproic acid[2] for patients with co-existing convulsions. We administrated long-acting injectable olanzapine with beneficial prophylactic effects, lowering the severity of manic and depressive symptoms to a set of milder ones without severe catatonic features such as excitement, stupor, or negativism.…”
mentioning
confidence: 99%